Intensified Tuberculosis Case-Finding in HIV-Positive Adults Managed at Ethiopian Health Centers: Diagnostic Yield of Xpert MTB/RIF Compared with Smear Microscopy and Liquid Culture - Balcha, Taye T. (Public Library of Science, 2014)
BACKGROUND: Detection of active tuberculosis (TB) before antiretroviral therapy (ART) initiation is important, but optimal diagnostic methods for use in resource-limited settings are lacking. We assessed the prevalence of TB, evaluated the diagnostic yield of Xpert MTB/RIF in comparison with smear microscopy and culture, and the impact of Xpert results on clinical management in HIV-positive adults eligible for ART at health centers in a region of Ethiopia. METHODS: Participants were prospectively recruited and followed up at 5 health centers. Trained nurses collected data on socio-demographic characteristics, medical history and symptoms, and performed physical examination. Two paired morning sputum samples were obtained, and lymph node aspirates in case of lymphadenopathy. Diagnostic yield of Xpert MTB/RIF in sputum was compared with smear microscopy and liquid culture. RESULTS: TB was diagnosed in 145/812 participants (17.9%), with bacteriological confirmation in 137 (16.9%). Among bacteriologically confirmed cases, 31 were smear-positive (22.6%), 96 were Xpert-positive (70.1%), and 123 were culture-positive (89.8%). Xpert MTB/RIF increased the TB detection rate by 64 cases (47.4%) compared with smear microscopy. The overall sensitivity of Xpert MTB/RIF was 66.4%, and was not significantly lower when testing one compared with two samples. While Xpert MTB/RIF was 46.7% sensitive among patients with CD4 cell counts >200 cells/mm(3), this increased to 82.9% in those with CD4 cell counts ≤100 cells/mm(3). Compared with Xpert-positive TB patients, Xpert-negative cases had less advanced HIV and TB disease characteristics. CONCLUSIONS: Previously undiagnosed TB is common among HIV-positive individuals managed in Ethiopian health centers. Xpert MTB/RIF increased TB case detection, especially in patients with advanced immunosuppression. An algorithm based on the use of a single morning sputum sample for individuals with negative sputum smear microscopy could be considered for intensified case finding in patients eligible for ART. However, technical and cost-effectiveness issues relevant for low-income countries warrant further study.